The Contagion and Copycat Effect in Transnational Far-right Terrorism: an Analysis of Language Evidence - Kupper, Julia (Perspectives on terrorism, 2022)
This article corroborates the continued threat of extreme right terrorism by exemplifying textually interconnected links across linguistic evidence composed prior to or during attacks in the United States, New Zealand, Germany, Norway and Sweden. A qualitative content analysis of targeted violence manifestos and live-streams, attack announcements on online platforms, and writings on equipment (e.g., firearms) used during the incidents reveals an emerging illicit genre set that is increasingly consolidated in form and function. The messages accentuate an intricate far-right online ecosystem that empowers copycats and escorts them on their pathway to violence. A definition for targeted violence live-streams is proposed and operational applications are discussed.